The Effect of Corporate Governance Mechanisms and Bank-Specific Factors on the Financial Performance of Commercial Banks in Nepal - Dongol, Padam (MVIC Journal of Management and Information Technology, 2025)
This study investigates the impact of corporate governance mechanisms and bank-specific factors on the financial performance of Nepalese commercial banks. The research examines five banks from 2016/17 to 2022/23, focusing on two corporate governance mechanisms—board size and capital adequacy ratio—and three bank-specific factors: dividend payout ratio, firm size, and nonperforming loan ratio. Data for the study were gathered from secondary sources, including publications and annual reports of banks listed on the Nepal Stock Exchange (NEPSE). A purposive sampling method was used to select five merged banks for analysis. Descriptive analysis, Pearson correlation, and multiple regression models were employed to assess the relationships between the variables and the return on assets (ROA), which served as the dependent variable. The findings indicate that board size positively and significantly affects ROA, while firm size has a significant negative impact. However, capital adequacy ratio, dividend payout ratio, and non-performing loan ratio do not show significant effects on ROA. Thus, the study offers valuable insights for regulators, managers, depositors, and other stakeholders, contributing to improved performance and profitability of integrated commercial banks in Nepal.